Brina the Cat - 1 #1, The gang of the feline sun - Salati, Giorgio 1978-; Cornia, Christian 1975-; Clemente, Massimiliano; Aureli, Alessandro; Doni, Olivia Rose (New York : Papercutz, 2020)
"Brina, a city cat, moved to the mountains with the owners for a summer holiday. Here she meets some stray cats who call themselves "The Gang of the Feline Sun". The new friends convince her to escape her owners and become a free cat. But while Brina enjoys her newfound freedom and all the new types of delectable bugs the countryside has to offer, her young owners are panicking over losing her, a member of their family. Brina must make a choice to live with her owners, where it's safe (but confined) or go in the wilderness. A heartwarming tender cat tale."--Provided by publisher.
Keywords: Pets -- Comic books, strips, etc; Cats -- Comic books, strips, etc; Cats -- Fiction; Pets -- Fiction